2017
DOI: 10.5935/0103-507x.20170008
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease exacerbation in the intensive care unit: clinical, functional and quality of life at discharge and 3 months of follow up

Abstract: ObjectiveThe purpose of this study was to evaluate the clinical/functional aspects and quality of life of chronic obstructive pulmonary disease patients who were discharged after an intensive care unit admission for acute respiratory failure.MethodsThis prospective study included chronic obstructive pulmonary disease patients who were admitted to two intensive care units between December of 2010 and August of 2011 and evaluated over three visits after discharge. Thirty patients were included, and 20 patients c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Dodd et al [11] also found no improvement in cognitive performance at 3-months post-discharge using a comprehensive neuropsychological assessment. However, there are inconsistencies in methodology across studies and, as such, other studies have shown an improvement in cognition following recovery [15,17,18]. These methodological differences make direct comparisons between studies difficult, as the timings of the baseline assessment (e.g.…”
Section: Recovery In Patients Following Aecopdmentioning
confidence: 99%
See 3 more Smart Citations
“…Dodd et al [11] also found no improvement in cognitive performance at 3-months post-discharge using a comprehensive neuropsychological assessment. However, there are inconsistencies in methodology across studies and, as such, other studies have shown an improvement in cognition following recovery [15,17,18]. These methodological differences make direct comparisons between studies difficult, as the timings of the baseline assessment (e.g.…”
Section: Recovery In Patients Following Aecopdmentioning
confidence: 99%
“…Processing speed, language and attention have all found to be impaired following hospitalisation for an exacerbation [11,13,17], however the recovery of cognitive performance and other health markers 1-3 months post-discharge is unclear. Viana et al [15] identified a significant improvement from discharge to the stable phase, however all patients remained mildly cognitively impaired following a 3-month recovery period. This CI could influence decision-making and self-management, such as a patient's decision to accept the offer of pulmonary rehabilitation (PR).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations